Kesantunan Berbahasa dalam Komunikasi Daring di Kalangan Mahasiswa (Studi pada Prodi Pendidikan Bahasa Indonesia Universitas Sindangkasih Majalengka): (Studi pada Prodi Pendidikan Bahasa Indonesia Universitas Sindangkasih Majalengka) - Sari, Endah Meilani (JBI : Jurnal Bahasa Indonesia, 2025)
Politeness in digital communication is a crucial aspect that reflects students' sociolinguistic competence in the digital era. This study is motivated by the low awareness among students of the Indonesian Language Education Study Program at Universitas Sindang Kasih Majalengka in applying principles of politeness when interacting through digital media. Common issues include the use of informal language, non-standard abbreviations, and emotional tones in academic conversations. This research aims to describe the forms of language politeness used by students, identify influencing factors, and analyze the application of politeness principles in online interactions between students and lecturers as well as among peers. A qualitative descriptive method was employed, with data collected through in-depth interviews, observation of digital interactions on platforms such as WhatsApp class groups, and document analysis in the form of chat screenshots. The findings indicate that students have not fully grasped the ethics of academic digital communication, as shown by weak pragmatic understanding and low awareness of polite language use. Contributing factors include the culture of instant communication and lack of guidance. Thus, integrating digital communication ethics into the curriculum and encouraging lecturers to model polite communication are essential to foster an ethical and professional digital academic environment.